A)2h+(5h+3hy)=2h+5h+3hy=7h+3hy
Б)2h-(4h+9h)=2h-4h-9h=2h-13h=-11h
B)6h^2y-(3h^2y-5h^2y)=6h^2y-3h^2y+5h^2y=8h^2y
Г)(5hy-6hy)+(8hy-2hy)=-1hy+6hy=5hy
Д)(-7h^3-7h^3)-(2hh^3+9)=-14h^3-2h^4+9
E)-(2yh+7)-(9hy-6)=-2hy-7-9hy+6=-11hy-1
Ж)-(-3y^3h^5-12hy)+(-hy+8y^3h^5)=3y^3h^5+12hy-hy-8y^3h^5=-5y^3h^5+11hy
З)(2h-19)-(18+6h-5h)=2h-19-18-6h+5h=h-37
И)(-9hy-4h)+(-3h-8hy)=-9hy-4h-3h-8hy=-hy-7h
3p^2-12p-p^2-4
^ -степень
Я сделаю 2 задание , 1 пример
(4x-3)^2-6x (4-x)=16x^2-24x+9-(24x-6x^2)=16x^2-24x+9-24x+6x^2=22x^2-48x+9
Надеюсь , это правильно